CHEMICAL COMPOSITIONS AND THE PHYTOCHEMICAL CONSTITUENTS OF THE SEED OF SESAMUM INDICUM GROWN AT KATSINA STATE, NORTHERN NIGERIA - Datti, Y.; Barau, S. S.; Nura, T. (FUDMA JOURNAL OF SCIENCES, 2023)
The seeds of Sesamum indicum (sesame) are one of the oldest sauce, relish and spice known to man. This study determines the chemical composition (both proximate and the mineral contents), as well as the phytochemical constituent of the variety of sesame seed available in Katsina State, Nigeria. The proximate and phytochemical analyses were carried out using standard procedures, while the mineral content was determined by atomic absorption spectrophotometry. The results for the proximate content of the analysed sesame seeds are moisture 7.63%; crude protein 21.34%; crude fibre 9.54%; crude lipid 41.84%; ash 9.01% and carbohydrate 10.64%. The seeds were also found to contain some minerals including Na 0.37%; K 1.69%; Mg 0.32%; Ca 1.12%; P 0.76%; Zn 0.0073%; Cu 0.038%; Mn 0.0026 and Fe 0.021%. The results for the phytochemical screening revealed the presence of alkaloids, carbohydrates, flavonoids, phytosterols, proteins, saponins and terpenoids, while tannins were found to be absent. The present findings suggest that sesame seeds can be a good source of nutrients in the diet and may have health and economic benefits due to its fibre and minerals content, as well as its phytochemical contents.
Keywords: Sesamum indicum, phytochemicals, proximate analysis, mineral content